(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents a comprehensive analysis of physiological markers as instruments for determining an individual`s biological age. The significance of the topic has been substantiated by the growing concern over population aging, increased life expectancy, and the pressing need to transition toward personalized preventive medicine. The development of the concept of biological age has been examined, tracing its progression from early assessment attempts to contemporary molecular and integrative approaches, including the study of epigenetic clocks (mathematically derived indicators of biological age) and cutting-edge technologies for multiparametric evaluation. A classification of existing methods for assessing biological age has been provided, encompassing cellular and molecular markers, clinical biomarkers, functional assessments, and complex integrative scales. Particular emphasis has been placed on physiological markers of aging – parameters reflecting the condition of the cardiovascular, respiratory, musculoskeletal, metabolic, immune, and endocrine systems. Normative values, typical age-related changes, and the prognostic relevance of these markers for health outcomes have been outlined. The practical applications of physiological markers have been studied across various domains: in gerontology, for monitoring the aging process and formulating individualized strategies for active longevity; in clinical medicine, for predicting risks of cardiovascular and metabolic diseases; in sports science, for evaluating training efficacy, managing physical load, and preventing overtraining; and in personalized medicine, for tailoring therapeutic interventions based on an individual’s physiological condition rather than chronological age. The article emphasizes the critical role of physiological markers in the future development of health sciences, aging research, and medical practice, highlighting their contribution to the establishment of a healthcare model centered on preventive, personalized, and predictive principles. It concludes by emphasizing the potential of further research integrating physiological and cognitive indicators to enhance biological age assessment and to devise effective strategies for mitigating aging processes, particularly among younger populations.